2016
DOI: 10.18632/oncotarget.7261
|View full text |Cite
|
Sign up to set email alerts
|

A plasma proteolysis pathway comprising blood coagulation proteases

Abstract: Coagulation factors are essential for hemostasis. Here, we show that these factors also team up to degrade plasma proteins that are unrelated to hemostasis. Prolidase, SRC and amyloid β1-42 (Aβ1-42) are used as probes. Each probe, upon entering the blood circulation, binds and activates factor XII (FXII), triggering the intrinsic and common coagulation cascades, which in turn activate factor VII, a component of the extrinsic coagulation cascade. Activated factor VII (FVIIa) rapidly degrades the circulating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…We recently found that PEPD is a ligand of ErbB1 and ErbB2 which are oncogenic receptor tyrosine kinases, that the enzymatic function of PEPD is not needed for this activity, and that intracellular PEPD has no effect on these receptors 8 10 . It remains unclear about the physiological importance of PEPD as a ligand of ErbB1 and ErbB2 or the involvement of these receptors in PD, as circulating PEPD level is kept low by a plasma proteolysis pathway 11 . However, recombinant human PEPD or an enzymatically inactive mutant, when added to cell culture or injected to tumor-bearing mice (with inhibition of the plasma proteolysis pathway), strongly inhibits the growth of cancer cells overexpressing ErbB1 and/or ErbB2 9 , 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that PEPD is a ligand of ErbB1 and ErbB2 which are oncogenic receptor tyrosine kinases, that the enzymatic function of PEPD is not needed for this activity, and that intracellular PEPD has no effect on these receptors 8 10 . It remains unclear about the physiological importance of PEPD as a ligand of ErbB1 and ErbB2 or the involvement of these receptors in PD, as circulating PEPD level is kept low by a plasma proteolysis pathway 11 . However, recombinant human PEPD or an enzymatically inactive mutant, when added to cell culture or injected to tumor-bearing mice (with inhibition of the plasma proteolysis pathway), strongly inhibits the growth of cancer cells overexpressing ErbB1 and/or ErbB2 9 , 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…FVII is a serine protease produced in the liver and presents in plasma as a zymogen at a concentration of 10 nM (0.5 µg/ml) [10][11][12] . This vitamin K-dependent glycoprotein is circulating in plasma in two forms, mainly as inactive single-chain zymogen and partly as active form (FVIIa) consisted of heavy and light chains.…”
Section: Coagulation Factor VIImentioning
confidence: 99%
“…Aβ also binds to and activates coagulation factor XII (FXII), which can then initiate the contact system [3943], a proteolytic cascade that leads both to clot formation through the intrinsic coagulation pathway and also to inflammation via bradykinin release after high molecular weight kininogen (HK) cleavage. Aβ-mediated activation of FXII could be one mechanism behind the increased contact system activation observed in the plasma and CSF of AD patients and mouse models [39, 40]…”
Section: The Fxii Contact System Is Significant In Ad Pathophysiologymentioning
confidence: 99%